2018
DOI: 10.1111/hel.12532
|View full text |Cite
|
Sign up to set email alerts
|

The association of garlic with Helicobacter pylori infection and gastric cancer risk: A systematic review and meta‐analysis

Abstract: Pooled evidence, mainly from case-control studies, suggested a significant inverse association of garlic intake with gastric cancer risk. Given the limitations of included studies, current epidemiological evidence is not sufficient to reach any definite conclusion regarding the association of garlic with Helicobacter pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Among the 31 studies, 11 studies (Chiavarini et al, ; Fleischauer et al, ; Guercio et al, ; Hu et al, ; Kodali & Eslick, ; Li et al, ; Turati et al, , ; Zhou et al, , ; Zhu et al, ) were about cancer and tumor outcomes (gastric cancer, colorectal cancer, upper aerodigestive tract cancer, prostate cancer, and colorectal adenomatous polyps), 13 studies (Emami et al, ; Khoo & Aziz, ; Kwak et al, ; Reinhart et al, ; Ried, ; Ried, Toben, et al, ; Sahebkar et al, ; Shabani et al, ; Stevinson et al, ; Sun et al, ; Wang et al, ; Warshafsky et al, ; Zeng et al, ) were about metabolic outcomes (serum total cholesterol [TC], high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], triglycerides [TGs], fasting blood glucose [FBG], serum HbA1c, serum fructosamine, serum lipoprotein (a), and apolipoprotein B), seven studies (Reinhart et al, ; Ried, ; Ried et al, ; Rohner et al, ; Silagy & Neil, ; Wang et al, ; Xiong et al, ) were about cardiovascular outcomes (systolic blood pressure and diastolic blood pressure), and only one systematic review and meta‐analysis (Taghizadeh et al, ) was about serum C‐reactive protein levels. Finally, 50 unique outcomes extracted from the 16 most recent meta‐analyses were analyzed in this umbrella review, and the map of allium vegetable‐related outcomes is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 31 studies, 11 studies (Chiavarini et al, ; Fleischauer et al, ; Guercio et al, ; Hu et al, ; Kodali & Eslick, ; Li et al, ; Turati et al, , ; Zhou et al, , ; Zhu et al, ) were about cancer and tumor outcomes (gastric cancer, colorectal cancer, upper aerodigestive tract cancer, prostate cancer, and colorectal adenomatous polyps), 13 studies (Emami et al, ; Khoo & Aziz, ; Kwak et al, ; Reinhart et al, ; Ried, ; Ried, Toben, et al, ; Sahebkar et al, ; Shabani et al, ; Stevinson et al, ; Sun et al, ; Wang et al, ; Warshafsky et al, ; Zeng et al, ) were about metabolic outcomes (serum total cholesterol [TC], high‐density lipoprotein [HDL], low‐density lipoprotein [LDL], triglycerides [TGs], fasting blood glucose [FBG], serum HbA1c, serum fructosamine, serum lipoprotein (a), and apolipoprotein B), seven studies (Reinhart et al, ; Ried, ; Ried et al, ; Rohner et al, ; Silagy & Neil, ; Wang et al, ; Xiong et al, ) were about cardiovascular outcomes (systolic blood pressure and diastolic blood pressure), and only one systematic review and meta‐analysis (Taghizadeh et al, ) was about serum C‐reactive protein levels. Finally, 50 unique outcomes extracted from the 16 most recent meta‐analyses were analyzed in this umbrella review, and the map of allium vegetable‐related outcomes is reported in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Then, 19,023 articles remained after removing the duplicates, and 18,992 articles were excluded after reviewing the titles and abstracts. Finally, 31 full-text articles (Chiavarini et al, 2016;Emami, Rouhani, & Azadbakht, 2017;Fleischauer, Poole, & Arab, 2000;Guercio, Turati, La Vecchia, Galeone, & Tavani, 2016;Hu et al, 2014;Khoo & Aziz, 2009;Kodali & Eslick, 2015;Kwak et al, 2014;Li, Ying, Shan, & Ji, 2018;Reinhart, Coleman, Teevan, Vachhani, & White, 2008;Reinhart, Talati, White, & Coleman, 2009;Ried, 2016;Ried, Frank, Stocks, Fakler, & Sullivan, 2008;Ried, Toben, & Fakler, 2013;Rohner, Ried, Sobenin, Bucher, & Nordmann, 2015;Sahebkar et al, 2016;Shabani et al, 2018;Silagy & Neil, 1994;Stevinson, Pittler, & Ernst, 2000;Sun, Wang, & Qin, 2018;Taghizadeh, Hamedifard, & Jafarnejad, 2018;Turati et al, 2014;Turati, Pelucchi, Guercio, La Vecchia, & Galeone, 2015;Wang, Yang, Qin, & Yang, 2015;Wang, Zhang, Lan, & Wang, 2017;Warshafsky, Kamer, & Sivak, 1993;Xiong et al, 2015;Zeng et al, 2012;Zhou, Ding, & Liu, 2013;Zhou et al, 2011;Zhu, Zou, Qi, Zhong, & Miao, 2014) were reviewed for further assessment.…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garlic has beneficial effects on gastric and intestinal cancers. A study by the Chinese Academy of Medical Sciences found that there was an inverse relationship between the consumption of garlic and the incidence of gastric cancer (Li, Ying, Shan, & Ji, ). Garlic prevents the growth of cancer by increasing the activity of natural killer (NK) cells and macrophages (Grudzien & Rapak, ).…”
Section: A Sativummentioning
confidence: 99%
“…Garlic has beneficial effects on gastric and intestinal cancers. A study by the Chinese Academy of Medical Sciences found that there was an inverse relationship between the consumption of garlic and the incidence of gastric cancer (Li, Ying, Shan, & Ji, 2018).…”
Section: Garlic Cytotoxicity and Apoptosis-inducing Effectsmentioning
confidence: 99%